The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1111/1532-7795.00042
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Early Adolescence: Their Relations with Classroom Problem Behavior and Peer Status

Abstract: It has been suggested that early antisocial behavior plays a causal role in the development of depression during childhood and adolescence through pervasive failures in social competence and social acceptance (Patterson & Capaldi, 1990). The present study was conducted to test this hypothesis by examining longitudinal data from a sample of 215 Italian middle school students. Analyses revealed that time-one problem behavior predicted both time-two peer status and time-two depressive symptoms, even after control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
116
4
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 35 publications
(42 reference statements)
10
116
4
5
Order By: Relevance
“…Indeed, in recent analyses from the Child Development Project, Lansford et al (2003) found that early peer rejection was not related to later depressive symptoms when children's concurrent levels of aggression were controlled, suggesting that the relation between peer rejection and later depressive symptoms may be due, in large part, to cooccurring externalizing problems. Kiesner (2002), on the other hand, did find unique covariation between peer relations and depression when controlling for such antisocial behavior. These results highlight the importance of controlling for potential confounds in studies examining the relation between peer problems and children's depressed mood.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 78%
“…Indeed, in recent analyses from the Child Development Project, Lansford et al (2003) found that early peer rejection was not related to later depressive symptoms when children's concurrent levels of aggression were controlled, suggesting that the relation between peer rejection and later depressive symptoms may be due, in large part, to cooccurring externalizing problems. Kiesner (2002), on the other hand, did find unique covariation between peer relations and depression when controlling for such antisocial behavior. These results highlight the importance of controlling for potential confounds in studies examining the relation between peer problems and children's depressed mood.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 78%
“…The link between rejection at school and development of psychological problems such as depression and stress has been well established in studies both using cross-sectional (Coie, Lochman, Terry, & Hyman, 1992) and longitudinal designs (Kiesner, 2002;Kiesner, Poulin, & Nicotra, 2003), both for aggressive and nonaggressive rejected students (Hecht, Inderbitzen, & Bukowski, 1998); however, nonaggressive rejected students usually obtain higher scores in measures of loneliness, shyness, and worries about being rejected again compared to aggressive rejected students (Parkhurst & Asher, 1992).…”
Section: Personal Variablesmentioning
confidence: 99%
“…Academic competence was related to declines in depressive symptoms and emotional distress across elementary school years (Herman, Lambert, Ialongo, & Ostrander, 2007;Roeser, Eccles, & Sameroff, 2000). Similarly, broad indices of social competence such as social problems, peer status, and sociability predicted stability in internalizing symptoms across childhood and adolescence with lower social competence forecasting increases in symptoms (Chen, Li, Li, Li, & Liu, 2000;Kiesner, 2002;Mesman et al, 2001). Furthermore, studies indicate that longitudinal decline in academic and social competence predicted higher levels of current internalizing symptoms (Chen, Rubin, & Li, 1995;Cole, Martin, & Powers, 1997;Kellam, Rebok, Mayer, Ialongo, & Kalodner, 1994).…”
mentioning
confidence: 93%